Kepemimpinan Kyai Dalam Meningkatkan Kualitas Pendidikan Pesantren: Studi Kasus di Yayasan Pesantren Nasyrul Ulum Al-Aziziyah - Muzaffar, Ilham (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze kyai leadership in managing and improving the quality of education at Nasyrul Ulum Al-Aziziyah Islamic Boarding School Samalanga. The research focuses on the leadership style applied by the kyai and the strategies implemented to improve the quality of pesantren education. The research uses a qualitative approach with a single case study method. Data collection techniques were conducted through participatory observation, in-depth interviews with kyai, ustadz (teachers), foundation administrators, students (santri), and the community, as well as documentation. Data analysis used qualitative descriptive analysis techniques with stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that Abi Zulfikar Imran's leadership style combines authoritarian and charismatic leadership, referred to as charismatic authority. The kyai serves not only as a spiritual leader but also as a manager who integrates Islamic values with modern management. The strategies implemented include enhancing educator competencies through mindset transformation, developing curriculum that integrates salafi curriculum with formal curriculum, building infrastructure and facilities, strengthening evaluation systems, and empowering students through motivation and participation in various competitive activities. The implications of kyai leadership include improved spiritual education quality, better-structured organization, character building of students, good social interaction with the community, innovation in teaching methods, and attention to student welfare. This research concludes that effective kyai leadership is capable of mobilizing all elements of the pesantren to achieve the goal of improving educational quality. The success of kyai leadership is supported by the ability to combine traditional approaches with modern innovation and build harmonious communication with all stakeholders.